Pencegahan Pernikahan Dini melalui Edukasi dan Konseling - A.Fatimah Jamir; Andi Tenri Angka; Ummu Kalsum; Wati; Sarifah Syahira (Manfaat : Jurnal Pengabdian Pada Masyarakat Indonesia, 2025)
Early marriage remains a significant issue in Indonesia, including in South Sulawesi, with negative impacts on health, education, and social welfare. These impacts include high school dropout rates, reproductive health issues, and increased maternal and infant mortality rates. This community service activity aims to provide education and counseling to second-semester students of the Faculty of Business at Universitas Mega Buana Palopo regarding the dangers of early marriage and the importance of future planning. The methods used in this activity include lectures, group discussions, and individual counseling. Through the lectures, students were provided with information about the health, social, and psychological risks associated with early marriage. Group discussions aimed to enhance students' understanding and awareness of the importance of education and future planning before marriage. Additionally, individual counseling was conducted to provide more personalized support related to issues students might face. The results of the activity showed an increase in students' knowledge and awareness of the negative impacts of early marriage, as well as a positive attitude toward preventing early marriage. This activity is expected to serve as a sustainable campus-based early marriage prevention model that can be applied to other universities. With proper education and counseling, it is hoped that students will make wiser decisions regarding marriage and future planning. Improved knowledge will reduce the prevalence of early marriage and mitigate its negative effects on individuals and society.